Hedge funds and their implications for financial stability - Tomas Garbaravicius; Frank Dierick (European Central Bank (ECB), 2005)
The paper provides an overview of the hedge fund industry, mainly from a financial stability and European angle. It is primarily based on an extensive analysis of information from the TASS database. On the positive side of the financial stability assessment, hedge funds have a role as providers of diversification and liquidity, and they contribute to the integration and completeness of financial markets. Possible negative effects occur through their impact on financial markets (e.g. via crowded trades) and financial institutions (e.g. via prime brokerage). Several initiatives have been launched to address these concerns and most of them follow indirect regulation via banks. If any direct regulation were to be considered, it would probably have to be implemented in a coordinated manner at the international level. At the EU level there is currently no common regulatory regime, although some Member States have adopted national legislation.
Keywords: G15; G18; G21; G23; G24; 330; Asset management; crowded trades; financial regulation; financial stability; hedgefunds; prime brokerage; risk management.; Finanzmarkt; Geldpolitik; Portfolio-Management; Risikomanagement; EU-Staaten; Hedgefonds